2023
DOI: 10.1080/21645515.2023.2283315
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of COVID-19 boosters among hypertensive patients in China: A multicenter cross-sectional study

Ying Yan,
Qingyuan Chen,
Abudulimutailipu Nuermaimaiti
et al.

Abstract: Hypertension, a prevalent chronic disease, has been associated with increased COVID-19 severity. To promote the COVID-19 booster vaccination of hypertensive patients, this study investigated the willingness to receive boosters and the related influencing factors based on the health belief model (HBM model). Between June and October 2022, 453 valid questionnaires were collected across three Chinese cities. The willingness to receive a booster vaccination was 72.2%. The main factors that influenced the willingne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…The survey showed that the participants had received vaccination-related information from HCWs, also in combination with a variety of other sources, as the most used source. This result corresponds to findings obtained in other similar surveys conducted in this and in other geographic areas [ 28 , 39 , 40 , 41 , 42 ]. Moreover, the results of the multinomial and multivariate logistic regression analysis demonstrated that HCWs were the most important communication source in disseminating accurate information about vaccinations aimed at mitigating the risk and other public health threats.…”
Section: Discussionsupporting
confidence: 92%
“…The survey showed that the participants had received vaccination-related information from HCWs, also in combination with a variety of other sources, as the most used source. This result corresponds to findings obtained in other similar surveys conducted in this and in other geographic areas [ 28 , 39 , 40 , 41 , 42 ]. Moreover, the results of the multinomial and multivariate logistic regression analysis demonstrated that HCWs were the most important communication source in disseminating accurate information about vaccinations aimed at mitigating the risk and other public health threats.…”
Section: Discussionsupporting
confidence: 92%